Comparison of the Expression of Hepatic Genes by Human Wharton’s Jelly Mesenchymal Stem Cells Cultured in 2D and 3D Collagen Culture Systems - Zahra Khodabandeh (Iranian Journal of Medical Sciences, 2016)
Background: Human Wharton’s jelly mesenchymal stem cells (HWJMSCs) express liver-specific markers such as albumin, alpha-fetoprotein, cytokeratin-19, cytokeratin-18, and glucose-6-phosphatase. Therefore, they can be considered as a good source for cell replacement therapy for liver diseases. This study aimed to evaluate the effects of various culture systems on the hepatocyte-specific gene expression pattern of naïve HWJMSCs. Methods: HWJMSCs were characterized as MSCs by detecting the surface CD markers and capability to differentiate toward osteoblast and adipocyte. HWJMSCs were cultured in 2D collagen films and 3D collagen scaffolds for 21 days and were compared to control cultures. Real time RT-PCR was used to evaluate the expression of liver-specific genes. Results: The HWJMSCs which were grown on non-coated culture plates expressed cytokeratin-18 and -19, alpha-fetoprotein, albumin, glucose-6-phosphatase, and claudin. The expression of the hepatic nuclear factor 4 (HNF4) was very low. The cells showed a significant increase in caludin expression when they cultured in 3D collagen scaffolds compared to the conventional monolayer culture and 2D collagen scaffold. Conclusion: Various culture systems did not influence on hepatocyte specific marker expression by HWJMSCs, except for claudin. The expression of claudin showed that 3D collagen scaffold provided the extracellular matrix for induction of the cells to interconnect with each other.